Д КРОЗВИТОК ДУАЛЬНОЇ ФОРМИ ОСВІТИ В УКРАЇНІ У СПІВПРАЦІ З НІМЕЦЬКИМИ ОРГАНІЗАЦІЯМИ (Innovative professional education, 2023)
In connection with the attention to the dual form of education in Ukraine, it will be appropriate to investigate the main areas of work of Ukraine and its partners in the implementation of the dual form of education. The main projects and concepts in the implementation of this form of professional education with the support of German and European organizations are highlighted.
Keywords: dual education, international organizations, training, support, cooperation